1974
DOI: 10.1017/s0043174500036808
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Herbicide-Crop Rotation on Nutsedge, Annual Weeds, and Crops

Abstract: In a 3 year herbicide-crop rotation involving corn (Zea maysL. ‘Coker 811A’), cotton (Gossypium hirsutumL. ‘Carolina Queen’), and peanuts (Arachis hypogaeaL. ‘Argentine’), uncontrolled yellow nutsedge (Cyperus esculentusL.) and annual weeds drastically reduced all crop yields. By the end of the rotation sequences, intensive cultivation throughout the rotation killed 97 to 99% of the nutsedge tubers, but this level of control depended on hand-weeding the cotton. Moderate application of herbicides killed from 78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

1974
1974
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 6 publications
1
34
0
Order By: Relevance
“…Cultivation can effectively reduce nutsedge populations, but it must be done thoroughly and often for 2 to 3 years (Hauser et al. , 1974; Stoller et al.…”
Section: Discussionmentioning
confidence: 99%
“…Cultivation can effectively reduce nutsedge populations, but it must be done thoroughly and often for 2 to 3 years (Hauser et al. , 1974; Stoller et al.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the studies that do exist often focus on very different questions. For example, a small number of studies compare rotations to monocultural systems (Table 1), while others compare two or more rotations (e.g., Dunham et al 1958, Kampf 1969 or the effects ofvarious weed control practices applied to a single rotation (e.g., Hauser et al 1974, Menges 1987. In several studies (e.g., Montemurro and Trotta 198311984, Berea and Ionescu 1988), a set of treatments without herbicides has not been included so that it is impossible to separate the effects of the rotation itself from the rotation of herbicides superimposed upon it.…”
Section: Weed Suppression Through Crop Rotationmentioning
confidence: 99%
“…Because corn, cotton, and grain sorghum are the major rotational crops with peanut in Texas, growers could use the imidazolinone-resistant corn varieties or metolachlor in their herbicide programs to reduce yellow nutsedge densities. Crop rotation can be an effective cultural nutsedge control practice (Hauser et al 1974;Johnson and Mullinix 1997). Hauser et al (1974) showed that with intensive weed management in a 3-yr cotton-corn-peanut rotation, the number of yellow nutsedge tubers can be reduced at least 97% from that of the untreated check.…”
Section: Resultsmentioning
confidence: 99%
“…Crop rotation can be an effective cultural nutsedge control practice (Hauser et al 1974;Johnson and Mullinix 1997). Hauser et al (1974) showed that with intensive weed management in a 3-yr cotton-corn-peanut rotation, the number of yellow nutsedge tubers can be reduced at least 97% from that of the untreated check. Johnson and Mullinix (1997) reported that cultivation is as effective as intensive weed management systems of yellow nutsedge control in corn.…”
Section: Resultsmentioning
confidence: 99%